Engaging patients as partners in a multicentre trial of spinal versus general anaesthesia for older adults. (February 2021) - Hruslinski, Jennifer; Menio, Diane A.; Hymes, Robert A.; Jaffe, J. Douglas; Langlois, Christine; Ramsey, Lolita; Gaskins, Lakisha J.; Neuman, Mark D.; ,; Looke, Thomas; Bent, Sandra; Franco-Mora, Ariana; et al.
Summary: Engaging patients—defined broadly as individuals with lived experience of a given condition, family members, caregivers, and the organisations that represent them—as partners in research is a priority for policymakers, funders, and the public. Nonetheless, formal efforts to engage patients are absent from most studies, and models to support meaningful patient engagement in clinical anaesthesia research have not been previously described. Here, we review our experience in developing and implementing a multifaceted patient engagement strategy within the Regional Versus General Anesthesia for Promoting Independence After Hip Fracture (REGAIN) surgery trial, an ongoing randomised trial comparing spinal vs general anaesthesia for hip fracture surgery in 1600 older adults across 45 hospitals in the USA and Canada. This strategy engaged patients and their representatives at both the level of overall trial oversight and at the level of individual recruiting sites. Activities spanned a continuum ranging from events designed to elicit patients' input on key decisions to longitudinal collaborations that empowered patients to actively participate in decision-making related to trial design and management. Engagement activities were highly acceptable to participants and led to concrete changes in the design and conduct of the REGAIN trial. The REGAIN experience offers a model for future efforts to engage patients as partners in clinical anaesthesia research, and highlights potential opportunities for investigators to increase the relevance of anaesthesia studies by incorporating patient voices and perspectives into the research process.